Reviving Architectural Heritage: Restorations and Cultural Implications of the Jome Mosque in Kukon: Menghidupkan Warisan Arsitektur: Restorasi dan Implikasi Budaya Masjid Jome di Kukon - Iskanderov Sultanbek (Academia Open, 2023)
This study examines the historical renovations and cultural implications of the Jame Mosque in Kukon, a significant architectural monument. Through an analysis of various accounts from historical works such as "History of Fargona" and "History of Turkestan," we investigate the restoration efforts carried out under different rulers, including Omar Khan and Olim Khan, and the challenges encountered during these processes. The restoration methods employed ranged from uncovering original paintings to replacing rotted mosque pillars. The results indicate that the successive restorations not only preserved the mosque's cultural and architectural significance but also served as a catalyst for the city's transformation into a renowned center for scholars and visitors. Ultimately, this research highlights the importance of preserving architectural heritage and its impact on the cultural identity and community development of Kukon.Highlights: Restoration of the Jame Mosque significantly contributed to preserving Kukon's architectural and cultural heritage. Challenges faced during restoration included inexperienced craftsmen and the use of low-quality materials. The mosque's preservation and transformation positively impacted Kukon's community development and reputation as a center for scholars and visitors. Keywords: Jome Mosque, Kukon, architectural heritage, restoration efforts, cultural implications